VoIP Technology: Applications and Challenges - Chakraborty, Tamal; Misra, Iti Saha; Prasad, Ramjee (Springer Series in Wireless Technology, 2019)
This book offers an accessible introduction and practical guide to Voice over Internet Protocol (VoIP) technology, providing readers with the know-how to solve the problems encountered in applying VoIP technology across all types of network. It incorporates the latest research findings and brings readers up to date with the challenges that are faced by researchers developing novel applications of VoIP. The authors discuss the general architecture of VoIP technology, along with its application and relevance in conventional and emerging wireless communication networks, including Wireless Local Area Networks (WLANs), Worldwide Interoperability for Microwave Access (WiMAX), Long Term Evolution (LTE) and Cognitive Radio Networks. The book also includes Quality of service (QoS) studies under dynamic and unpredictable network conditions, which examine the reliability of both legacy systems And the upcoming pervasive computing systems. Further, it explains how the heuristic-based learning algorithms that are used in VoIP communications may help develop today's technology in the area of autonomous systems. This book is a valuable source of information for academics and researchers, as it provides state-of-theart research in VoIP technology. It is also of interest to network designers, application architects, and service providers looking for a coherent understanding of VoIP across a wide range of devices, network applications and user categories.